If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(c + -8) = c + 4 Reorder the terms: 3(-8 + c) = c + 4 (-8 * 3 + c * 3) = c + 4 (-24 + 3c) = c + 4 Reorder the terms: -24 + 3c = 4 + c Solving -24 + 3c = 4 + c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-1c' to each side of the equation. -24 + 3c + -1c = 4 + c + -1c Combine like terms: 3c + -1c = 2c -24 + 2c = 4 + c + -1c Combine like terms: c + -1c = 0 -24 + 2c = 4 + 0 -24 + 2c = 4 Add '24' to each side of the equation. -24 + 24 + 2c = 4 + 24 Combine like terms: -24 + 24 = 0 0 + 2c = 4 + 24 2c = 4 + 24 Combine like terms: 4 + 24 = 28 2c = 28 Divide each side by '2'. c = 14 Simplifying c = 14
| 2.73x^2+1.47x-5.72=0 | | 141-7x=29x+21 | | y=0.75x | | x^4-2x^2-63=0 | | 50x^2-8=0 | | 10x+6=7x+18 | | 9x+1=9x+1 | | 5x^2-30x+25=0 | | 4x-9x-16=-5x+9-16 | | (5+p)-(p-q)-(3p+4q-6)= | | 5x-7=5(x+7) | | X^2-5X+40=0 | | 10(n+3)=2(15+5n) | | 10x-9+9x-5=9x-3 | | 2x-128=0 | | 2h^2+13h-7=0 | | (6x-3)+(3x+2)= | | 99-2x=5x+22 | | 5(x+9)+5(-6x-1)=-26(x-1) | | 4x-3=5+12x | | 5x+25= | | 1.2x-6=0 | | 12x-7-x-10=15x+8+x-3 | | 245(82X-56)=517X+2134 | | 16y^2=81 | | n^2+7n+14=5 | | x^2-3=-2 | | 25h^2-16=0 | | 3x^2+8x-9=2x | | 6x+15=4x+29 | | 64k^2-49=0 | | x^2+9x+160=0 |